2005
DOI: 10.1096/fj.05-3904fje
|View full text |Cite
|
Sign up to set email alerts
|

A cell‐based high‐throughput assay for screening inhibitors of human papillomavirus‐16 long control region activity

Abstract: Cervical carcinomas express human papillomavirus (HPV) E6 and E7 oncoproteins, which are required to maintain the proliferative state of cancer cells. Repression of E6 and E7 expression results in acquisition of senescent phenotype and in the rescue of functional p53 and p105(Rb) pathways; therefore, therapies directed against either viral protein may be beneficial. However, the systems to study HPV in vitro are technically difficult and not convenient for screening of antiviral compounds. This has hampered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The results of the present study showed that IFN-γ induces TLR3 expression and enhances anti-viral activity in NHEKs. IFN-γ alone, IFN-β, and some antimicrobial peptides have also anti-viral activities (Hazrati et al, 2006;Lembo et al, 2006;Crack et al, 2012;Wilson et al, 2013). Among them, IFN-β is reported to be the major factor responsible for anti-viral activity in human keratinocytes (Torseth et al, 1987;Fujisawa et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study showed that IFN-γ induces TLR3 expression and enhances anti-viral activity in NHEKs. IFN-γ alone, IFN-β, and some antimicrobial peptides have also anti-viral activities (Hazrati et al, 2006;Lembo et al, 2006;Crack et al, 2012;Wilson et al, 2013). Among them, IFN-β is reported to be the major factor responsible for anti-viral activity in human keratinocytes (Torseth et al, 1987;Fujisawa et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…High-risk Intraepithelial neoplasia and cervical cancer 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 68, 73, 82 (26, 53, 66) Low-risk Intraepithelial neoplasia or genital warts 6,11,40,12,43,44,53,54,61,72,73,81 HPV particles are composed by a non-enveloped icosahedral capsid that shields the viral genome. The HPV genome consists of a single circular double-stranded DNA (dsDNA) molecule associated with host-derived histones, and, typically, encodes seven to eight open reading frames (ORFs) (Figure 1).…”
Section: Group Type Of Lesions Hpv Typesmentioning
confidence: 99%
“…It was reported that several cytokines, namely IL-1α, IL-4 IL-13, transforming growth factor β (TGF-β), tumor necrosis factor α (TNF-α), IFN-α and IFN-β, act as inhibitors of HPV16 URR activity, suppressing early gene transcription [54]. Furthermore, type I IFNs, TNF-α and TGF-β restrain the growth of non-infected and HPV-infected keratinocytes, while this suppression tends to cease in oncogenic cells [55,56].…”
Section: Activation Of the Antiviral Immune Signallingmentioning
confidence: 99%
“…KC constitutively secrete low levels of soluble immune mediators, including cytokines, chemokines, and growth factors (46)(47)(48), the production of which can be elevated in response to proinflammatory stimuli, including PRR activation and autocrine or paracrine stimulation with inflammatory cytokines (31,43,46,47,49). Several cytokines, including type I IFNs, TNF-␣, IL-1␣, IL-4, IL-13, and transforming growth factor ␤ (TGF-␤), share the ability to inhibit HPV early gene expression (50)(51)(52)(53)(54). In addition, type I IFNs, TNF-␣, and TGF-␤ suppress the growth of normal KC and nontumorigenic, HPV-transformed KC, although effectiveness can vary with the transforming HPV type and is generally lost with progression to a tumorigenic phenotype (50,51,54,55).…”
Section: Kc As Mediators Of Innate Immunitymentioning
confidence: 99%